2014
DOI: 10.1007/s10157-014-1064-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics of M-type phospholipase A2 receptor (PLA2R)-related membranous nephropathy in Japanese

Abstract: Assessments of both serum PLA2R antibodies and PLA2R antigen in glomeruli were more sensitive for the diagnosis of PLA2R-related MN, and among affected Japanese patients, those with dominant IgG4 deposition had worse clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 26 publications
4
24
1
1
Order By: Relevance
“…However, as shown in this study, because the positivity of anti-PLA2R antibodies is affected by many factors, such as the phase and severity of the disease, and the detection methods, it is not clear whether there is truly a difference in the prevalence of anti-PLA2R antibodies among patients with primary MN based on ethnicity. Interestingly, Hayashi et al reported that serum anti-PLA2R antibodies were positive according to western blot in 12/22 (55%) of the Japanese patients with primary MN while four out of the 10 primary MN patients with no detectable serum anti-PLA2R antibodies had glomerular PLA2R deposits [20]. Thus, 16 patients (73%) were classified in the PLA2R-related group when combined.…”
Section: Discussionmentioning
confidence: 99%
“…However, as shown in this study, because the positivity of anti-PLA2R antibodies is affected by many factors, such as the phase and severity of the disease, and the detection methods, it is not clear whether there is truly a difference in the prevalence of anti-PLA2R antibodies among patients with primary MN based on ethnicity. Interestingly, Hayashi et al reported that serum anti-PLA2R antibodies were positive according to western blot in 12/22 (55%) of the Japanese patients with primary MN while four out of the 10 primary MN patients with no detectable serum anti-PLA2R antibodies had glomerular PLA2R deposits [20]. Thus, 16 patients (73%) were classified in the PLA2R-related group when combined.…”
Section: Discussionmentioning
confidence: 99%
“…However, IgG4 does not bind C1q and is considered to be unable to activate the classical pathway [26,27]. The presence of IgG1 in early deposits could possibly activate the classical pathway, but C1q deposits are very weak in MN [28]. This suggests that the alternative or lectin pathways might be involved in complement activation.…”
Section: Introductionmentioning
confidence: 99%
“…Serum PLA2R antibodies in adult patients with MN have been widely studied by many nephrologists in the North American and European countries[ 7 16 ], and the Asian countries including China [ 17 21 ], but the data of PLA2R staining, especially accompanied with IgG subclasses staining, in renal biopsy tissues of large series of adult MN patients are relatively limited [ 13 17 , 22 ]. In this study, the glomerular deposits of PLA2R and IgG subclasses in a large series of Chinese patients with PMN and SMN were retrospectively studied by using immunofluorescence and immunohistochemical staining, and the potential value of these examinations for differential diagnosis of PMN and SMN was explored.…”
Section: Introductionmentioning
confidence: 99%